Living Law, Kepastian Hukum, dan Hak Asasi Manusia: Politik Hukum dalam KUHP 2023 di Indonesia - Ario, Dion; Situngkir, Swandi Aliverchan; Situngkir, Fernandes; Elviandri (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
The recognition of living law in Indonesia’s 2023 Criminal Code (KUHP 2023) has sparked significant debate regarding its compatibility with the principle of legality and human rights protection. Existing studies largely approach this issue descriptively, leaving a gap in normative analysis concerning the transformation of legality and its constitutional limits. This study critically examines the incorporation of living law in the KUHP 2023 by analyzing its implications for the shift from formal legality toward material legality and the resulting tension between legal certainty, human rights, and communal justice. Employing normative legal research, this study applies statutory, conceptual, and philosophical approaches, drawing on theories of material legality, legal pluralism, and constitutionalism. The analysis focuses on relevant provisions of the KUHP 2023, legal doctrines, and international human rights principles to assess the conditions and limits of applying living law within criminal law. The findings reveal that the recognition of living law represents a deliberate move toward a socially responsive criminal justice system. However, this shift also generates inherent human rights challenges, particularly concerning the foreseeability of criminal norms and the risk of arbitrary enforcement. This study argues that such tensions cannot be eliminated but must be managed through constitutional interpretation, judicial restraint, and human rights–based oversight. The study contributes a normative framework for balancing legality, human rights protection, and communal justice within Indonesia’s plural legal system, offering guidance for legislators, judges, and law enforcement authorities.